The Effect of Debt Policies, Intellectual Capital, and Corporate Governance Mechanisms on Firm Value in Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Desmizar, Desmizar (Baca Dulu Publisher, 2025)
This study aims to determine the effect of debt policy, intellectual capital, and good corporate governance mechanisms on firm value. Indicators used to measure good corporate governance mechanisms in this study is the managerial ownership, institusional ownership, and independent commissioner. Debt policy variable is measured using debt to equity ratio, intellectual capital variables are measured using the Pulic model (1998), while the variable firm value is measured using Tobin’s Q. The population in this study is the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2020-2023 period were 34 companies. The sample in this study was taken using a purposive sampling method and obtained as many as 33 sample companies. This study uses multiple linear regression analysis and descriptive statistics processed with SPSS 22. The results showed that the variable of debt policy, intellectual capital and independent commissioner variables have a significant effect on firm value. The results also prove that managerial ownership and institusional ownership do not have significant effect on firm value.